Hepatic inflammatory myofibroblastic tumor: One case report - Shen, Lei; Yang, Zixuan; Ding, Ruibo; Wei, Wei; Xu, Yechuan (Frontiers in Surgery, 2022)
Introduction：Hepatic inflammatory myofibroblastic tumor (HIMT) is a junctional neoplastic lesion of mesenchymal tissue origin that can sometimes become locally invasive and even metastasize or recur. Therefore, the diagnosis and treatment of HIMT is particularly important. However, hepatic inflammatory myofibroblastic tumor lacks a specific clinical presentation and typical imaging manifestations, thus posing a difficulty for us to diagnose and treat this disease. Case Presentation: We report here a very rare surgical case of hepatic inflammatory myofibroblastic tumor (HIMT) in a 41-year-old female who was admitted to the hospital for more than half a month for a liver-occupying lesion with fever found on physical examination.After discussion with the hepatobiliary and pancreatic surgery team, we decided to perform surgical treatment.The final postoperative pathology confirmed hepatitis myofibroblastoma. Conclusion:Our review of the domestic and international literature revealed no significant progress in the diagnosis and treatment of this disease, so we report here a case of surgical treatment. One of our aims in this case report is to highlight the efficacy of surgical treatment in HIMT. HIMT is extremely rare and difficult to diagnose. Due to their intermediate biological behavior, surgical resection should be performed whenever feasible and patients should be followed-up in order to detect recurrence and metastasis as early as possible.